Verification of Distributed Energy Resource Models for Microgrid Fault Calculations - Nikola Simić; Luka Strezoski; Simiša Simić; Dušan Čohadžić (Energija, Ekonomija, Ekologija)
The emerging microgrids are mainly powered by renewable distributed energy resources (DERs), such as solar and wind, with batteries as a backup power. These DERs are decoupled from the grid by inverters and thus, their fault currents are dictated by the control strategies programmed in the inverter itself. The inverters’ control strategies are in most cases dictated by the Grid Code requirements, in order to help the microgrid ride through the fault as painless as possible. Thus, in order to have accurate results for microgrid fault calculations, crucially important for setting the relay protection and protecting the entire microgrid, these DERs must be accurately modelled. Unfortunately, these models have not yet been fully developed nor standardized. In this paper, a recently developed model for inverter-based DERs are integrated into the fault current calculation based on the IEC 60909 standard for fault calculations and tested in the state-of-the-art hardware-in-the-loop environment. The test results are very promising, which opens the possibility to standardize these novel models, filling the seriously dangerous gap of not having the standardized fault models for inverter-based DERs.